So viel Mathe muss sein! : Gut vorbereitet in ein WiMINT-Studium /: Gut vorbereitet in ein WiMINT-Studium. (2019) - Dürrschnabel, Klaus; Dürr, Rolf; Erben, Wolfgang; Gercken, Matthias; Lunde, Karin; Wurth, Rita; Zimmermann, Marc
No abstract available